Mechanisms underlying neutrophil adhesion to apical epithelial membranes - Meenan, J; Mevissen, M; Monajemi, H; Radema, S A; Soule, H R; Moyle, M; Tytgat, G N; van Deventer, S J (Gut, 1996)
Crypt abscesses allow prolonged apposition of activated neutrophils to the epithelial surface of the colon. Adhesion of neutrophils to both the vascular endothelium and basolateral epithelial membrane share common effector molecules but are distinct processes. This study aimed to define the mechanisms that effect adhesion, independent of transmigration, to the apical epithelium. HT29 (cl 19A) cells were grown to confluency and incubated with neutrophils under conditions of: (i) neutrophil stimulation with phorbol-myristate-acetate; (ii) monolayer stimulation with interferon gamma, tumour necrosis factor alpha (IFN gamma, TNF alpha); and (iii) recent epithelial cell trypsinisation. These experiments were carried out in the presence of neutralising antibodies to CD18, CD11b, LFA-1, E-selectin, P-selectin, intracellular adhesion molecule 1 (ICAM-1), and ICAM-2; a novel CD11b/CD18 antagonist, neutrophil inhibitory factor (rNIF); adenosine receptor agonists (5'N-ethycarboxamido adenosine/N6-cylopentyladenosine (NECA/CPA)) and a platelet activating factor (PAF) receptor antagonist lexipafant. Adhesion of stimulated neutrophils to resting monolayers was Mac-1, CD18 dependent and ICAM-1, ICAM-2, E-selectin, P-selectin, PAF independent. Cytokine activated monolayers exhibited higher binding of neutrophils which was inhibited by rNIF and aCD18. Recently trypsinised monolayers bound neutrophils in a CD11b/CD18 and CD18 independent manner. Adenosine agonists failed to influence neutrophil adhesion under any condition. This study shows neutrophil adhesion to apical epithelial membranes is similar to that at the epithelial basolateral membrane, though different to that seen at the vascular endothelium. These results highlight regional differences in neutrophil adhesion molecule usage.